Revitalization of BLKK to Achieve Sustainable Independence through Synergy and Diversification of Funding Sources - Nuraeni, Yeni; Yuliastuti, Ari; Nasution, Faizal Amir P; Iqbal, Faizul (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2024)
This research aims to overcome the challenges of sustainability and suitability of Community Job Training Centers (BLKK) in meeting the needs of a rapidly growing job market. With a focus on diversifying funding sources and strengthening synergies between the government, private sector and community, this research develops an adaptive BLKK sustainability model to improve the quality of human resources relevant to industrial needs. A qualitative approach with case studies analyses BLKKs that have achieved independence, highlighting independent funding, partnerships with the business world, and good governance. The research results identified BLKK's main challenges, including dependence on government funding, the need for partnerships with the business world, and limited resource management. It was found that successful BLKKs have characteristics such as transparent governance, strategic partnerships with the business world, and diversification of funding sources. This research suggests policies that can increase institutional capacity, strengthen collaboration with the private sector, and encourage diverse funding sources to reduce dependence on government funds.